Collective motion of chiral Brownian particles controlled by a circularly-polarized laser beam. Issue 33 (31st July 2020) - Hernández, Raúl Josué; Sevilla, Francisco J.; Mazzulla, Alfredo; Pagliusi, Pasquale; Pellizzi, Nicola; Cipparrone, Gabriella
Abstract : Remote switching from passive to collective chiral-active motion by circularly-polarized light is shown for spherical polymeric Brownian particles. Light-propulsion is triggered by the coupling between the particle's chirality and the light helicity. Abstract : We demonstrate the emergence of circular collective motion in a system of spherical light-propelled Brownian particles. Light-propulsion occurs as consequence of the coupling between the chirality of polymeric particles – left ()- or right ()-type – and the circularly-polarized light that irradiates them. Irradiation with light that has the same helicity as the particle material leads to a circular cooperative vortical motion between the chiral Brownian particles. In contrast, opposite circular-polarization does not induce such coupling among the particles but only affects their Brownian motion. The mean angular momentum of each particle has a value and sign that distinguishes between chiral activity dynamics and typical Brownian motion. These outcomes have relevant implications for chiral separation technologies and provide new strategies for optical torque tunability in mesoscopic optical array systems, micro- and nanofabrication of light-activated engines with selective control and collective motion.